Psychological Manipulation in Benoît Delhomme’s Mothers’ Instinct (2024): A Psychoanalytic and Behavioral Perspective (Sastra Inggris UNPAM, 2025)
Manipulation as a psychological phenomenon often manifests through subtle emotional tactics that distort a victim’s perception of reality. Mothers’ Instinct (2024), directed by Benoît Delhomme, presents a compelling portrayal of this phenomenon through the complex relationship between two mothers, Céline and Alice. The research problem addressed in this study concerns how manipulation is constructed cinematically in the film and how such behavior psychologically impacts the victim. The primary data consist of selected scenes, dialogues, character expressions, and cinematographic elements from Mothers’ Instinct, which were analyzed to identify both the manipulative tactics used and their psychological consequences. Employing a qualitative approach, the analysis integrates Sigmund Freud’s (1923) psychoanalytic theory to explore unconscious motivations and George K. Simon’s (1996) modern psychological framework to classify manipulation tactics. The study focuses on two analytical dimensions: (1) the internal psychological drives that shape Céline’s manipulative behaviors, and (2) the external strategies she employs to exert control over Alice. The findings reveal that manipulation in the film is primarily conveyed through gaslighting and guilt-tripping, both of which operate covertly to destabilize the victim’s emotional balance. These tactics result in significant psychological effects on Alice, most notably reality confusion and anxiety, which impair her ability to assess events objectively. The study highlights how cinema can effectively dramatize psychological manipulation and underscores the broader implications for understanding emotional coercion in interpersonal relationships, particularly within contexts of grief and trauma.